PENGARUH KEPUASAN KEPEMILIKAN MEMBERSHIP CARD TERHADAP LOYALITAS PENGUNJUNG PADA MODERN RETAILDI YOGYAKARTA - Alfa Santoso Budiwidjojo Putra (Jurnal Riset Manajemen dan Bisnis, 2012)
This study aims to examine the effect of ownership satisfaction to loyalty membership card in the modern retail visitors in Yogyakarta. Thisstudy used 102 respondents as a sample of consumers who are visiting at the modern retail. While the sampling technique used is a combination of snowball sampling technique and purposive sampling. The results showed that the satisfaction of the benefits of discount, ease of service satisfaction, and satisfaction with the service special influence on modern retail visitor loyalty, while satisfaction with the service doesn’t influence on the visitor loyalty.Keywords:satisfaction and visitor loyalty